2020
DOI: 10.1007/s00417-020-04734-4
|View full text |Cite
|
Sign up to set email alerts
|

HIF-1α, HIF-2α, and ProExC: diagnostic or prognostic relevance in conjunctival intraepithelial neoplasia?

Abstract: The aim of this study was to investigate HIF-1α, HIF-2α, and ProExC expression in conjunctival intraepithelial neoplasia (CIN), to differentiate between metaplasia and dysplasia, and to access their value as diagnostic and prognostic immunohistochemical markers. Recurrence and progression into SCC (squamous cell carcinoma) were defined as endpoints. Methods Forty-three specimens including CIN I (2), CIN II (9), CIN III (29), with and without metaplasia, and metaplasia alone (3), as well as 21 conjunctival cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 19 publications
0
2
1
Order By: Relevance
“…With regard to prognosis and treatment associated with molecular biological markers, other studies have examined the use of hypoxia-inducible factor-α (HIF-α) as a potential marker. [20] However, in the present study, HIF-α staining was not confirmed in preliminary our experiment(data not shown) and thus could not be used to obtain additional knowledge. Daubon et al reported that transforming growth factor 1 induced thrombospondin-1 expression via Smad3, which contributes to the invasive behavior during expansion found in glioblastoma development.…”
Section: Discussioncontrasting
confidence: 61%
“…With regard to prognosis and treatment associated with molecular biological markers, other studies have examined the use of hypoxia-inducible factor-α (HIF-α) as a potential marker. [20] However, in the present study, HIF-α staining was not confirmed in preliminary our experiment(data not shown) and thus could not be used to obtain additional knowledge. Daubon et al reported that transforming growth factor 1 induced thrombospondin-1 expression via Smad3, which contributes to the invasive behavior during expansion found in glioblastoma development.…”
Section: Discussioncontrasting
confidence: 61%
“…For instance, traumatic brain injury in rats resulted in significant HIF1α elevation detected as early as 1 h after the trauma [ 22 ]. We had found similar results when immunohistochemically comparing immunoreactivity of both HIF isoforms in conjunctival intraepithelial neoplasia (CIN) and in healthy conjunctiva, and assumed that HIF is downregulated in CIN to avoid cell cycle arrest and HIF-induced apoptosis, because all cells of the conjunctiva, even if dysplastic, may be well oxygenated [ 13 ].…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Formalin fixation and paraffin embedding of pterygium and healthy conjunctiva specimens were performed immediately after surgery according to our routine protocols, as previously described [ 13 ]. Briefly, specimens were fixed in 4% formalin for 12 h, dehydrated in alcohol, and finally processed for paraffin embedding.…”
Section: Methodsmentioning
confidence: 99%